Optimalisasi Lubang Resapan Biopori untuk Pengelolaan Limbah Rumah Tangga - Weni Wilia; Dedy Antony (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2024)
The community that will be the target of the outreach activities are community members who are active in Islamic Education Institutions. The main activity is to educate students who aim to master the knowledge of the Quran and also teach Islamic morals in everyday life located in Penyengat Rendah Village, Telanai Pura District, Jambi City, Jambi Province. The activities that have been carried out are carrying out activities with the outreach method and followed by field practice and questions and answers regarding the material that has been given. The outreach material provided was about environmental and health aspects related to organic waste management activities and methods for making good and correct biopore infiltration holes that are environmentally friendly. The response from participants in this community service activity was seen to be positive and had a high enthusiasm to apply the knowledge that had been gained and were aware of the importance of environmental aspects that must be considered in waste management, especially organic waste. After this activity was carried out, it is hoped that the community can disseminate the information and knowledge that has been received to be applied to other communities.